Hybrid Waste to Energy Electricity Generation and Battery Storage System : The Economics and Environmental Emission in a Low-Income Community - Ahmed Abubakar, Elwan; Mohd Hafiz, Habibuddin; Yanuar Zulardiansyah, Arief; Ahmad Safawi, Mokhtar; Rasyidah, Mohamad Idris (Springer Nature Singapore Pte Ltd., 2024)
Waste and population growth have increased significantly, even in low income and developing countries. Gombe Metropolitan is the largest local government area in Gombe state, which is located in northern Nigeria. Gombe, like any other city in Nigeria, has seen an increase in population growth and land occupation, which has resulted in an increase in waste generation and a reduction in nearby land for landfilling activities. Using HOMER Pro optimization software, this study assesses the economic, environmental, and technical impact of a waste-to-energy (WtE) hybrid plant with a storage device. The system’s net present cost (NPC) is estimated to be $112,633 with a levelized cost of energy (LCOE) of 0.283$/kWh. The total energy generated is estimated to be 62,084 kWh/year, with an excess of 1049 kWh/year expected after consumption of 60,386 kWh/year. The simulation results show that the proposed system has a very significant impact on the environment, with very low emissions. The hybrid WtE/storage device system is not economically viable because the cost of electricity from the system is higher than the grid price, but the results show strong viability in terms of environmental impact.